Gaschromatographische Analyse des Samenfettes der mittelamerikanischen Fevillea Cordifolia (Cucurbitaceae) - Achenbach, Hans (1992)
The fat of the seeds of Fevillea cordifolia was extracted under exclusion of oxygen and light and then characterized by 13C-NMR in regard to the contained unsaturated acid moieties. The total fat was separated by HPLC to yield one major fraction (˜ 45%), one medium fraction (˜ 18%) and some minor fractions. All substantial fractions showed the chromophore of a conjugated triene. According to MS-analysis the major fraction consists of distearyleleostearylglycerol. The total fat was converted by transesterification to a mixture of fatty acids methyl esters, which was analyzed by subsequent HPLC and GC: Main fatty acids were found to be stearic acid (53%) and the triple conjugated α-eleostearic acid (31%). Interestingly, punicic acid, which is isomeric to α-eleostearic acid and contained in various seed fats of Cucurbitaceae plants, could not be detected.